2006
DOI: 10.1097/01.nrl.0000219637.83981.3c
|View full text |Cite
|
Sign up to set email alerts
|

Does Prior Aspirin Use Reduce Stroke Mortality?

Abstract: Daily low dose (100-300 mg) aspirin has a protective effect in reducing the risk of early death in stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Our results are consistent with previous reports that focused on aspirin showing significant benefit for APT users compared with non-users for the early functional prognosis, while there was a non-significant protective effect of APT on 1-month mortality [5][6][7]. Nevertheless, this association was not proved by other studies [4,8,9].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are consistent with previous reports that focused on aspirin showing significant benefit for APT users compared with non-users for the early functional prognosis, while there was a non-significant protective effect of APT on 1-month mortality [5][6][7]. Nevertheless, this association was not proved by other studies [4,8,9].…”
Section: Discussionsupporting
confidence: 88%
“…As a consequence, APT is common in patients at the time of their first-ever stroke, with a prevalence ranging from 26% to 38% according to data from population-based registries [1][2][3]. Several previous studies pointed out the fact that prestroke APT, especially aspirin, could affect both the early functional and vital prognosis of stroke patients [4][5][6][7][8][9][10][11][12][13]. However, most of these studies were limited either by a small population size, a hospital-based setting, a lack of control for potential confounding factors in multivariate analyses, or no differentiation between stroke subtypes, which probably contributed to the conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…The use of 75 mg ASA during the titration was set out to ensure that patients had a sufficient dosage of ASA during the 5-day titration phase as the combination tablet only contains 25 mg ASA and there is a consensus that at least 50 mg ASA daily is demanded for satisfactory stroke prevention [11]. …”
Section: Methodsmentioning
confidence: 99%
“…Our results indicate that heart dysfunction is not an independent predictor of all-cause mortality during long-term follow up in this cohort. Instead, we found that higher age, smoking, and pre-stroke myocardial infarction and none use of post-stroke aspirin [30-32] are independent predictors of mortality in patients with acute ischemic stroke or TIA, without atrial fibrillation. Lip et al [33] found that previous stroke/TIA was a predictor of mortality and of the composite end-point of stroke together with mortality in heart failure patients without atrial fibrillation, especially during the first 30 days following initial diagnosis of heart failure.…”
Section: Discussionmentioning
confidence: 78%